2021
DOI: 10.1007/s41465-021-00235-2
|View full text |Cite
|
Sign up to set email alerts
|

The Pursuit of Effective Working Memory Training: a Pre-registered Randomised Controlled Trial with a Novel Varied Training Protocol

Abstract: Working memory (WM) training, typically entailing repetitive practice with one or two tasks, has mostly yielded only limited task-specific transfer effects. We developed and tested a new WM training approach where the task paradigm, stimulus type, and predictability of the stimulus sequence were constantly altered during the 4-week training period. We expected that this varied training protocol would generate more extensive transfer by facilitating the use of more general strategies that could be applied to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…2 h 15 min) on our SOILE internet testing platform with their home computers or similar. In addition to the WM tasks and questionnaire items, the testing session included other cognitive tasks and questionnaires not reported here (for details, see Ritakallio et al 5 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 h 15 min) on our SOILE internet testing platform with their home computers or similar. In addition to the WM tasks and questionnaire items, the testing session included other cognitive tasks and questionnaires not reported here (for details, see Ritakallio et al 5 ).…”
Section: Methodsmentioning
confidence: 99%
“…To address these issues, the present study analysed self-reported strategy use in a number of WM tasks, its relationship with objective task performance, and its variation as a function of stimulus type and paradigm. We attempted an internal replication by performing these analyses in two previously acquired datasets 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation